Luminescence induced by elastic deformation of BaSi2O2N2:Eu crystals - Jha, P; Vhandra, V K; Chandra, B P (Recent Research in Science and Technology, 2012)
BaSi2O2N2:Eu is a very intense elastico-mechanoluminescent and photoluminescent materials. The microcrystalline BaSi2O2N2:Eu can be prepared using solid state reaction technique in reduced atmosphere. Then the microcrystalline phosphor was mixed epoxy and the samples of desired dimension size were prepared. For the ML excitation the sample was pressed using a material testing machine. When a compressive load is applied on the BaSi2O2N2:Eu sample, mixed in epoxy, then initially the elastico-mechanoluminescence (EML) intensity increases linearly with time, attains a peak value and later on it decreases with time. The recovery of EML intensity of previously to compressed crystals with ultraviolet light reveals non-destructive phenomenon of EML. The EML of BaSi2O2N2:Eu crystals can be understood on the basis of the piezoelectrically induced electron detrapping model.